DETERMINAN STRUKTUR MODAL PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ardhansyah Putra Hrp; Julianto Hutasuhut; M.Dhani Habra (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2024)
Funding decisions signal to the market about the condition of the company, so managers need to be careful in making decisions about the combination of funding sources called capital structure. The capital structure is a combination of debt and equity that is used to fund a company's activities. The mining sector is one of the industrial sectors that is able to attract investors, both domestic and foreign, to invest in Indonesia. Mining companies are capital-intensive industries, namely industries that are built with large capital and supported by high technology. However, to obtain funds from outside, the company must be careful about the loan so that an optimal capital structure is created. However, there is an inconsistency in the average capital structure and the factors that affect it every year, namely an increase or decrease in the average of several independent variables (profitability, company size, liquidity, and asset structure). Therefore, this research is important to determine the influence of profitability, company size, liquidity, and asset structure on the capital structure of mining companies listed on the Indonesia Stock Exchange (IDX). This study aims to see the influence of profitability, asset structure, liquidity, and company size on capital structure in the mining company sector listed on the Indonesia Stock Exchange for the 2018-2022 period. The population used in this study is 50 mining companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The data collection method uses purposive sampling using secondary data. The data were analyzed using multiple linear regression analysis techniques. The results of the study show that the profitability and asset structure of the company have no effect on the capital structure. Meanwhile, liquidity and company size affect the capital structure.